Solanezumab in‐depth outcomes: Results of the DIAN‐TU prevention trial of solanezumab and gantenerumab in dominantly inherited AD. (7th December 2020) - Farlow, Martin R.; Bateman, Randall J.; Aschenbrenner, Andrew J.; Benzinger, Tammie L.S.; Clifford, David; Coalier, Kelley; Cruchaga, Carlos; Fagan, Anne M.; Goate, Alison M.; Gordon, Brian A.; Hassenstab, Jason; Jack, Clifford R.; et al.
Abstract: Background: Solanezumab is a monoclonal antibody targeting soluble forms of β‐amyloid protein important in the pathogenesis of Alzheimer's disease (AD). Three previous 18‐month double‐blind placebo‐controlled trials of low‐dose solanezumab in late‐onset sporadic AD found inconsistent benefits on cognitive and functional assessments. Dominantly‐inherited mutation‐associated AD subjects both before and after onset of symptoms form an ideal population to study potential benefits of solanezumab therapy. Method: Mutation‐carrying asymptomatic (CDR 0, N=41) or mildly symptomatic (CDR 0.5 – 1, N=28) patients were treated for a minimum of 4 years and up to 7 years in a double‐blind 3 to 1 active versus placebo randomized clinical trial that measured disease progression by clinical, neuropsychological and biomarker evaluations. The trial was initiated with a dose of 400 mg every 4 weeks and escalated to 1600 mg when low dose trials in sporadic AD did not meet their primary endpoints. The primary cognitive outcome measure was DIAN‐MCE, composed of Delayed Recall Score of the International Shopping List Test, the Delayed Recall score of the Logical Memory IIa subtest from the Wechsler Memory Scale‐Revised, the Digit Symbol Substitution Test total score from the WAIS‐R and the MMSE total score. Secondary outcomes included a battery of other cognitive and functional measures. The study was powered to detect delay of cognitive disease progression in the DIAN‐MCE. Biomarkers include imaging modalities (volumetric MRI, FDG, amyloid and Tau PET). CSF markers included β‐amyloid, Tau and PhosphoTau species. NfL was measured in both CSF and plasma. The study used a pre‐specified Bayesian multivariate disease progression model, which included dynamic borrowing of control subjects from the DIAN Observational study. Result: The topline efficacy, safety and biomarker results will be reported. Conclusion: This study provides the first test of targeting soluble abeta forms in DIAD. It addresses the efficacy of early initiation of higher doses of solanezumab targeting soluble forms of amyloid as a disease modifying therapy. While these results are specific to DIAD, they have the potential to inform the application of anti‐amyloid therapy in sporadic AD.